Training and Development Human Resources Through Digital Skills at UMKM Bites Baker Malang - Putri, Selvia Sulaksana Andi; Nurhajati , Nurhajati; Sudaryanti, Dwiyani (FKIP - Universitas Riau, 2025)
Bites Baker is types of UMKM business cake making that focuses on brownies. The business Enough own potential in journey his efforts that the product Enough in demand Consumers . Training This aiming For give training and development of human resources for MSMEs through digital skills to be able to compete with similar SMEs and can increase HR performance at UMKM Bites Baker. The method used is descriptive with technique observation , companion , and evaluation . Research results show that Training This give knowledge UMKM owners and workers new about use digital technology for increase efficiency and productivity . HR learning management finance , digital marketing strategies , and tools soft management , which helps they optimize operation business. Digitalization technology in the HR development program provides benefit for MSMEs, such as improvement productivity and opportunities new For developing . This is motivate MSMEs to learn and innovate , which in turn increase economy them and society around.